Characteristics of Pruritus in Relation to Self-assessed Severity of Atopic Dermatitis - Flavien Huet; Marie-Sarah Faffa; Florence Poizeau; Stéphanie Merhand; Laurent Misery; Emilie Brenaut (Medical Journals Sweden, 2018)
The objective of this study was to explore characteristics of pruritus in atopic dermatitis (AD) in relation to the severity of AD. A web-questionnaire was used, which included the Patient-Oriented SCORing Atopic Dermatitis index, the 5-D itch scale and the Brest questionnaire. A total of 170 participants were included (86.5% women, mean age 30.9 years). Severity of AD was mild for 8.2% of patients, moderate for 38.2% and severe for 53.5%. Mean 5-D itch scale was 13.2. The mean intensity of pruritus was 5.8, and mean sleep loss was 4.7 (from 0 to 10). The participants frequently described burning (61.8%) and stinging (58.8%); these symptoms suggest a neuropathic component. Pruritus was worse in severe AD compared with moderate AD, exhibiting a higher impact on sleep and more associated symptoms. The majority of participants reported sleep disturbance as a result of pruritus. The characteristics of pruritus varied depending on the severity of AD.